Job evaluation: a basis for sound wage administration - Otis, Jay L.; Leukart, Richard H. (New York, Prentice-Hall, 1954)
The book examines the principles and meaning of various systems of job evaluation with case problems at the end of each chapter..
Includes index
Includes bibliography pp. 511-519
usc 28/01/2019
Loans
Keywords: Job analysis; Job evaluation